IMPLEMENTASI PENANAMAN KARAKTER ANAK DALAM SYAIR LAGU DOLANAN ANAK â€œCUBLAK-CUBLAK SUWENGâ€ - Endah Marwanti; Arya Dani Setyawan; Shanta Rezkita (Universitas Sarjanawiyata Tamansiswa, 2018)
The process of students’ character instillation was carried out in Masehi Temanggung elementary school to establish ethics, character and moral attitudes that can be used by the students as the role models in their environment. The characters that are intended to be established in Masehi Temanggung elementary school is the students’ character that is naturally established, in a sense that the change of the students’ behavior is due to their self-motivation based on what they do everyday; and not just merely due to the school obligation. The researchers employed qualitative approach method by observing thoroughly the students’ behavior occurred in the school setting. It is expected that the results from the direct observations will be able to portray the reality hidden in that situation. The evaluation method is used to analyze the information that is relevant to the students’ behavior at school and the next stage is classifying those data into two categories: first category is the students’ behavior that needs to be supervised and the second category is the students’ behavior that deserve the reward. In conclusion, making it as their habits can do the process of students’ character instillation. The students’ habits of good deeds are also carried out through games, for example by playing traditional games and toys (dolanan). There is a moral value implied in the traditional games and toys that is good to support the students’ character instillation.